Gambaran Sikap Ibu Hamil dalam Mencegah Keguguran - Sunarti Sunarti; Sri Winarni; Andre W. (Journal of Ners and Midwifery, 2016)
Miscarriage incident allegedly had an effect on the next pregnancy , either at the onset of complications of pregnancy and the outcome of pregnancy itself . Women with a history of miscarriage have a higher risk for preterm labor , recurrent miscarriage and low birth weight . The purpose of the research was to illustrates the attitude of pregnant women to prevent miscarriage with descriptive method . The population included all pregnant women who perform routine checks on Public Health Service UPTD Sananwetan Blitar during the period March 27 to 27 April 2014. The sample was 30 pregnant women first and second trimester with purposive sampling technique. The result was 53.3 % have a positive attitude , and 46.7 % have a negative attitude. It showed the attitude of pregnant women were lack in preventing miscarriage. There should be a more intensive outreach activities on the prevention of miscarriage by health employee to provide more detailed information, complete, and accurate.